Growth parameters of discordant preterm twins during the first year of life. (November 2014) - Mazkereth, Ram; Miron, Eitan; Leibovitch, Leah; Kuint, Jacob; Strauss, Tzipora; Maayan-Metzger, Ayala
Abstract Objective: To evaluate and compare growth parameters (weight, length and head circumference) of discordant preterm twins during the first year of life. Methods: Retrospective data were collected on 78 pairs of >10% discordant preterm twins. Data regarding short-term neonatal outcome were recorded. Growth parameters were recorded at birth and again at 1 year of age, as collected by phone interview. Results: At 1 year of age, the gap was significantly reduced between the group of smaller twins and the group of larger twins on all the parameters studied. Discordance in weight decreased from a mean of 22% at birth (calculated from the weight of the larger twin) to 8.9%, in length from 6.5% to 2.5% and in head circumference from 5.5% to 1.3% at 1 year of age. While length and head circumference (HC) z-scores improved in both the large and the small siblings, weight z-score decreased significantly among the large twins and decreased mildly among the small twins. Conclusions: The gaps in growth parameters between the smaller twins of preterm discordant twins and their larger siblings are significantly reduced during the first year of life. The impact of the differential growth patterns between the two siblings should be further evaluated.